Resilience and burden in caregivers of older adults: moderating and mediating effects of perceived social support - Ong, Hui Lin; Vaingankar, Janhavi Ajit; Abdin, Edimansyah; Sambasivam, Rajeswari; Fauziana, Restria; Tan, Min-En; Chong, Siow Ann; Goveas, Richard Roshan; Chiam, Peak Chiang; Subramaniam, Mythily (BMC psychiatry, 2018)
Background The burden of caring for an older adult can be a form of stress and influence caregivers’ daily lives and health. Previous studies have reported that resilience and social support play an important role in reducing physical and psychological burden in caregivers. Thus, the present study aimed to examine whether perceived social support served as a possible protective factor of burden among caregivers of older adults in Singapore using moderation and mediation effects’ models. Methods We conducted a cross-sectional study with 285 caregivers providing care to older adults aged 60 years and above who were diagnosed with physical and/or mental illness in Singapore. The Connor-Davidson Resilience Scale (CD-RISC) was used to measure resilience and burden was measured by the Zarit Burden Interview (ZBI). The Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure perceived social support. Hayes’ PROCESS macro was used to test moderation and mediation effects of perceived social support in the relationship between resilience and burden after controlling for sociodemographic variables. Indirect effects were tested using bootstrapped confidence intervals (CI). Results The mean scores observed were CD-RISC: 70.8/100 (SD = 15.1), MSPSS: 62.2/84 (SD = 12.2), and ZBI: 23.2/88 (SD = 16.0) respectively. While perceived social support served as a full mediator between resilience and caregiver burden (β = − 0.14, 95% CI -0.224 to − 0.072, p < 0.05), it did not show a significant moderating effect. Conclusions Perceived social support mediates the association between resilience and caregiver burden among caregivers of older adults in Singapore. It is crucial for healthcare professionals, particularly those who interact and deliver services to assist caregivers, to promote and identify supportive family and friends’ network that may help to address caregiver burden.